Teacher education in Singapore: Charting new directions - Saravanan, Gopinathan; Ponnusamy, Letchumy (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2011)
Singapore`s limited resources and need for extensive international engagement have privileged human capital development and thus made education a high policy priority to ensure its responsiveness and relevance. In three decades Singapore unified a fragmented teaching force, set high benchmarks for recruitment, preparation, deployment, and career development. Singapore`s present well-deserved reputation for educational quality, as represented in various international assessments of student achievement, can fairly be attributed to the quality of its teachers. Recognising the opportunities and challenges presented by globalisation, Singapore is seeking to transform its education system from an efficient, industrial era model into one more appropriate for the knowledge-economy. Major reforms are seeking to create more responsiveness to a variety of student needs, abilities and aspirations. There is now much more choice and multiple pathways, curriculum has been broadened, and assessment reforms are being considered. Recognising that such changes can only be successively implemented if teachers have both capacity and confidence, the Ministry has increased opportunities for professional upgrading while the National Institute of Education has redesigned the initial teacher preparation curriculum and introduced a new Masters in Teaching. A huge investment has also been made in education research to aid evidence informed policy and pedagogic change. In this paper we examine these changes in detail and assess prospects for successful and sustained change.